Resonant Raman Scattering of 4‐Nitrothiophenol. Issue 12 (27th October 2020) - Juergensen, Sabrina; Kusch, Patryk; Reich, Stephanie
Abstract : Thiophenol‐based molecules are commonly used reporter molecules for various experiments, especially within the scope of surface‐ and tip‐enhanced Raman spectroscopy. Due to their molecular structure, they bind covalently to noble metals and have a huge Raman scattering cross section. Herein, the widely uncharted optical properties of the frequently used probe molecule 4‐nitrothiophenol (p‐NTP or 4‐NTP) are analyzed by resonant Raman spectroscopy. Based on the three different types of samples, it is demonstrated that the molecule exhibits two intrinsic resonances at specific wavelengths. For a wide range of experiments, this is an important information since intrinsic resonances may give rise to an enhancement of the Raman intensity at these specific excitation wavelengths. The Raman cross section of p‐NTP in resonance at 1.9 eV (650 nm) to be 6 × 10 −26  cm 2 per molecule is also measured. Abstract : p‐nitrothiophenol (p‐NTP) is an often used reporter molecule for surface‐enhanced Raman spectroscopy (SERS) and tip‐enhanced Raman spectroscopy (TERS). By resonant Raman spectroscopy, it is shown that the molecule exhibits intrinsic resonances in the visible spectral range. Leading to an enhancement of the Raman signal, it is important to know the energetic location of the resonance for various spectroscopy methods.